Ice slurry ingestion during break times attenuates the increase of core temperature in a simulation of physical demand of match-play tennis in the heat - Naito, T.; Sagayama, H.; Akazawa, N.; Haramura, M.; Tasaki, M.; Takahashi, H. (Temperature, 2018)
This investigation assessed the effect of ice slurry ingestion compared to that of cold water ingestion during break times on thermal strain and perception in simulated match-play tennis in the heat. Seven male recreational athletes (age = 22 ± 2 yr, height = 1.72 ± 0.08 m, Body mass = 64.8 ± 6.8 kg) performed two trials in a climate chamber, each time completing 4 sets of simulated match-play. During International Tennis Federation-mandated breaks (90-s between odd-numbered games; 120-s between sets), either ice slurry or cold water were ingested. The rectal temperature, forehead skin temperature, heart rate, rating of thermal comfort and total sweat loss were measured. The change in rectal temperature in the ice slurry trial was significantly lower than that in the cold water trial by game 3 of set 3 (p = 0.02). These differences in ?rectal temperature persisted throughout the remainder of the "match" (p < 0.05). Forehead skin temperature, heart rate and rating of thermal comfort were significantly lower in the ice slurry trial than in the cold water trial by the second half of the experiment (p < 0.05). Total sweat loss in ice slurry trial is significantly lower than cold water trial (p = 0.002). These results suggested that ice slurry ingestion was more effective than cold water ingestion in mitigating the development of heat strain during simulated match-play tennis in the heat.